PENGARUH PEMBERIAN MIKROBA EFEKTIF PRODUKTIF PLUS (MEP+) PADA MEDIUM BUDIDAYA IKAN NILA YANG DIBERI PAKAN FERMENTATIF TERHADAP KEPADATAN BAKTERI ASAM LAKTAT - Nita Wulandari; Sukanto Sukanto; Endang Widyastuti (Scripta Biologica, 2014)
Microbes Effective Productive Plus (MEP+) in fish culture has role as probiotics and decomposer. Application of MEP+ is done by adding MEP+ on culture medium of Tilapia and fish feed. Fish feed is fermentative feed with addition of different concentration of cassava peel flour. The aim of this research were to find out the influence of MEP+ administration in culture medium and in fermentative feed with addition cassava peel flour on the increasing density of lactic acid bacteria in culture medium and find out the highest density of lactic acid bacteria. The research was done experimentally, used Complete Randomized Design with treatment of MEP+ administration in culture medium with fermentative feed cassava peel flour addition of 25%, 50%, 75% and without MEP+ administration on culture medium with fermentative feed cassava peel flour addition of 25%. The data obtained were analyzed using a variety analysis. The result showed that MEP+ administration on culture medium and in fermentative feed cassava peel flour addition did not influence the increasing density of lactic acid bacteria and total density of lactic acid bacteria in culture medium was not different inter treatment.